IMPLEMENTASI PROGRAM CSR DALAM PEMBERDAYAAN MASYARAKAT DI BIDANG BINA LINGKUNGAN PADA PERUSAHAAN PENYALURAN DAN PUSAT PENGATUR BEBAN SUMATERA (P3BS) (Studi Pada Kelompok Usaha Bayar Listrik Dengan Kotoran Sapi (Kubali Kopi) Di Desa Tanjung Lurah, Kecamata - Sapto Priyono; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The lack of knowledge held by rural communities and low educational owned makes them difficult to move forward in their efforts to pursue the field fully present namely agriculture, plantations and farms. To that end, this is where the role of PT PLN (Persero) Distribution and Load Control Center Sumatra present to provide assistance to exclude the public from its present state through the CSR program for Community Empowerment in the Field of Environmental Development. The program is known as the Kelompok Usaha Bayar ListrikDenganKotoranSapi (KubaliKopi). This study aims to determine the stage of implementation of CSR programs Kubali coffee and to investigate the impact of the implementation of the program Kubali Coffee on society as a receiver. This study uses qualitative research with descriptive approach which is located at the main office and the Load Distribution Center Sumatra (P3BS) at Jl. Nangka Edge, Kel. Anchoring the New West, district.Sekaki umbrella, Pekanbaru. This research was also carried out at the company's operations, In the village of TanjungLurah, Salimpaungsubdistrict, Tanah Datar Distict, West Sumatra Province. Starting from August to December 2016. The research subjects were 9 people. With the implementation of the research object KubaliKopiCSR program Perusahaan Penyaluran Dan PusatPengaturBeban Sumatera (P3BS). Data collection technique used, interviews, observation and documentation. Data analysis technique using descriptive qualitative data analysis according to Huberman and Miles.For technical data validity checking using an extension of participation and triangulation. The results of this study indicate public relations P3BS perform several stages in implementing CSR program Kubali Coffee are: First preceded by gathering facts. The facts collected in the form of data and information that will be processed, so diperolehlah a result. Second, formulating the problem, at this stage PR formulated three issues on the interpretation of the facts that have been collected are: One, How to change the mindset and habits of people to switch to using compost. Two, how to manage livestock manure which is owned by the public as compost.Three, How to develop alternative energy with the use of manure as a bio-gas power, amid the current energy crisis.Third, followed by planning and programming. At this stage PR required to plan an activity to answer the third formulation of the problem, ie, with activities including: socialization, development of facilities and infrastructure compost processing and infrastructure for the processing of bio-gas power. Fourth, action and communication, at this stage PR began to implement the activities. Fifth, the stage ditutp with FGD (Focus Group Discussion) to find out the results of the program viewed from three aspects, Environmental, Economic and Social Affairs.